Reflections on the Fukushima Daiichi Nuclear Accident Toward Social-Scientific Literacy and Engineering Resilience - Ahn, Joonhong; Carson, Cathryn; Jensen, Mikael; Juraku, Kohta; Nagasaki, Shinya; Tanaka, Satoru (Springer International Publishing : Imprint: Springer, 2015)
This book focuses on nuclear engineering education in the post-Fukushima era. It was edited by the organizers of the summer school held in August 2011 in University of California, Berkeley, as part of a collaborative program between the University of Tokyo and UC Berkeley. Motivated by the particular relevance and importance of social-scientific approaches to various crucial aspects of nuclear technology, special emphasis was placed on integrating nuclear science and engineering with social science. The book consists of the lectures given in 2011 summer school and additional chapters that cover developments in the past three years since the accident. It provides an arena for discussions to find and create a renewed platform for engineering practices, and thus nuclear engineering education, which are essential in the post-Fukushima era for nurturing nuclear engineers who need to be both technically competent and trusted in society.